Emotion Regulation as a Predictor of Juvenile Arrest - Kemp, Kathleen A. (Criminal justice and behavior, 2017)
The current study examines emotion regulation as a novel dynamic factor of juvenile arrest as it compares with known static and dynamic risk factors. Participants included seventh graders at five urban public schools (N = 420, Mage = 13, 53% male). The predictive relationship between adolescent self-, parent-, and teacher-report of baseline adolescent emotional competence and arrest at 30-month follow-up was assessed. Stepwise logistic regression analyses revealed that teacher report of emotion regulation strategies, minority status, and lifetime marijuana use were significant predictors of arrest. Findings indicate teacher report of emotion regulation competence in early adolescence may be an important consideration for prevention program development.